The effect of collectivism-oriented human resource management on employee resilience of hospitality employees - Chen, Shihua; Hu, Xiaohan; Xue, Yuting; Wang, Yuang (Frontiers in Psychology, 2024)
Introduction In the face of an increasingly challenging and rapidly evolving business environment, not all the employees exhibit the requisite resilience necessary to recover from adversity. From both the individual and organizational perspectives, enhancing employee resilience emerges as a critical issue not only in the practical and academic fields. In the Chinese culture, this research aims to investigate how and why collectivism-oriented human resource management (C-HRM) fosters employee resilience. Drawing on the group engagement model, we propose a serial mediating effect of perceived overall fairness and three dimensions of social identity between C-HRM and employee resilience. Methods Using a sample of frontline employees in the hospitality industry, we conducted a field survey among 342 employees (study 1) and a two-wave online survey among 294 hospitality employees (study 2). Results Findings from empirical analysis indicated that C-HRM significantly increases overall fairness perception of hospitality frontline employees and in turn, their identification and respect, which further fertilize employee resilience. In addition, the indirect effect of C-HRM on employee resilience through perceived overall fairness and pride was not statistically significant. Discussion These important findings are expected to help employees cope with the workplace pressures caused by ongoing challenges and change, and contribute to sustainable career development.